Efektivitas Pembelajaran Brain-Based Learning Terhadap Peningkatan Kemampuan Berpikir Logis Matematis Siswa - Suwarto; Lestari, Karunia Eka (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study aims to determine the effectiveness of brain-based learning on improving students' mathematical logical thinking abilities. The research uses a quantitative approach with a quasi-experimental method, specifically a non-equivalent control group design. The population in this study consists of all eighth-grade students at SMP Negeri 2 Karawang Timur. The sample includes two classes: Class VIII-G as the experimental group and Class VIII-J as the control group. The sampling technique used is cluster random sampling. Data collection was carried out using instruments in the form of pre-test and post-test. The instrument used in this study was a test designed to measure students' mathematical logical thinking abilities. There are two variables in this study: the use of the brain-based learning model as the independent variable and mathematical logical thinking ability as the dependent variable. The results of the study show that the post-test scores of the experimental class were higher than those of the control class, with N-Gain values of 0.50 and 0.45, respectively. The t-test for the difference in mean N-Gain scores showed a significance value (Sig. 2-tailed) < 0.05, namely 0.014, indicating that there was a significant difference in improvement between the control and experimental classes. Additionally, Cohen's d effect size (standardized mean difference) was 0.31, suggesting that the brain-based learning model had a moderately meaningful practical impact on improving students' mathematical logical thinking abilities. Thus, the brain-based learning model is proven to be effective both statistically and practically in enhancing students’ mathematical logical thinking skills.